2015
DOI: 10.4172/2155-9910.1000178
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Ecology and Prey Preference of Grey Mullet, Mugil cephalus (Linnaeus, 1758) in Extensive Brackish Water Farming System

Abstract: Feeding ecology and prey preference of Mugil cephalus reared in extensive brackish water farming system was studied based on monthly examination of stomach contents over a period of 10 months (February-November, 2014). Feeding intensity, planktonic constituents in water and food constituents in the stomach were estimated numerically. The percentage compositions of food items in the stomach falling under different groups were then compared with that of fish pond to evaluate prey preferences. Lower feeding inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
(23 reference statements)
1
14
0
1
Order By: Relevance
“…Concentrations of toxic metabolites like nitritenitrogen (NO2-N)and ammonia-nitrogen (NH4-N) remained lower than the critical level and concentrations of nutrients like nitrate-nitrogen (NO3-N) and phosphate-phosphorous (PO4-P) was much lower than fertilized ponds reported from Sundarbans [4,28] and corroborated with those reported earlier by Mondal et al [29] from the same location. Lower nutrient concentrations in the studied extensive system may be attributed to complete dependence on natural productivity without any additional input.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Concentrations of toxic metabolites like nitritenitrogen (NO2-N)and ammonia-nitrogen (NH4-N) remained lower than the critical level and concentrations of nutrients like nitrate-nitrogen (NO3-N) and phosphate-phosphorous (PO4-P) was much lower than fertilized ponds reported from Sundarbans [4,28] and corroborated with those reported earlier by Mondal et al [29] from the same location. Lower nutrient concentrations in the studied extensive system may be attributed to complete dependence on natural productivity without any additional input.…”
Section: Discussionsupporting
confidence: 80%
“…Fish and shrimp parts and dinoflagelets were not at all selected by L. parsia. Order of preference of phytoplanktonic food by L. parsia as myxophyceae>bacillariophyceae>chlorophyceae is different from coexisting species like Mugil cephalus L bacillario phyceae>myxophyceae>chlorophyceae [29] and Liza tade as ch lorophyceae>myxophyceae>bacillariophyceae [38] in the same environment suggests feeding strategy of mullets to reduce inter specific competition within the same tropic level.…”
Section: Discussionmentioning
confidence: 99%
“…Mullets have been reported that they are chiefly plankton feeders [49,50]. Bacillariophyceae followed by myxophyceae and Chlorophyceae as most dominant food constituents of M. cephalus in brackishwater environments have been reported from various parts of Indian subcontinent [7,51,52] and other parts of the world [53][54][55][56]. Planktonic algae were reported to be the dominant food item of gold spot mullet, L. parsia and planktonic groups according to the order of dominance were Chlorophyceae, Bacillariophyceae and Myxophyceae [57].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Mugil cephalus also observed preference for diatoms (Tandel et al, 1986;Khan and Fathima, 1994;Rao and Sivani, 1996;Bekova et al, 2013;Rao and Babu, 2013;Modou et al. 2014;Mondal et al, 2015). Blaber (1976) as well as Wijeyratnae and Costa (1990) noticed high proportion of sand in the stomachs of grey mullets.…”
Section: Weight Of the Gutmentioning
confidence: 91%
“…Grey mullets are typically bottom feeders subsisting on decayed organic matter, fresh and decaying algae and diatoms (Jacob and Krishnamurthy, 1948;Pillay, 1953;Bond, 1979;El-Marakby et al, 2006;Mondal et al, 2015). From the results obtained presently it is clear that the food of different size groups of L. subviridis largely comprise of decaying matter, sand, diatoms, dinoflagellates and zooplankton.…”
Section: Weight Of the Gutmentioning
confidence: 99%